2013
DOI: 10.1007/s00240-013-0596-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing non contrast computerized tomography criteria versus dual X-ray absorptiometry as predictors of radio-opaque upper urinary tract stone fragmentation after electromagnetic shockwave lithotripsy

Abstract: The objective of this study was to assess the value of dual X-ray absorptiometry (DXA) in comparison to non contrast computed tomography (NCCT) density as possible predictors of upper urinary tract stone disintegration by shock wave lithotripsy (SWL). This study included 100 consecutive patients, with solitary renal stone 0.5-2 cm or upper ureteral stone up to 1 cm. DXA to calculate stone mineral density (SMD) and stone mineral content (SMC) was done. NCCT was performed to measure Hounsfield units (HU). SWL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Consistent with previous studies [ 9 11 , 17 , 18 , 22 ], HU was a significant predictor of SFR after SWL in a multivariate analysis in our study. On the other hand, whether HN has an effect on the treatment outcome of SWL is controversial [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies [ 9 11 , 17 , 18 , 22 ], HU was a significant predictor of SFR after SWL in a multivariate analysis in our study. On the other hand, whether HN has an effect on the treatment outcome of SWL is controversial [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the numerous studies and great efforts to discover factors related to SWL outcomes [ 7 , 9 , 11 , 17 22 ], a clear general consensus has yet to be reached. Kanao et al [ 6 ] developed a nomogram to predict lithotripsy success based on stone size, location, and the degree of stone burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Hameed et al reported that successful outcome of ESWL was decreased in calculus with HU > 1350 and required application of more shock waves. [8] A study by Massoud et al reported that patients with Stone attenuation value (SAV) of > 956HU were not ideal candidate and SAV was an independent predictor of ESWL outcome. [9] Bandi et al found VSB to be strongest predictor of ESWL outcome in multivariate analysis (p< 0.001) in their study of patients with upper urinary tract calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Mapp et al (2016) and FAbOSA group (2002) did not present HU values. Nevertheless, other calcified structures are out of this range, e.g., scallop shells (744 HU) (Diez et al, 2013) and ureteral stone (1,350 HU) (Hameed et al, 2013).…”
Section: Exploring Otolith Density Variationmentioning
confidence: 99%